Telephone announcements encouraging common cold self-management reduce demand for general practice appointments. Issue 1 (16th February 2019) - Kerr, Robin; Grainger, Alan; Messer, Carol; Kerr, Hamish
Abstract : Background: Patients consulting with the common cold contribute to seasonal demand for general practice appointments. Seeing a community pharmacist or using self-management may have been more appropriate options. The study aimed to measure if the use of telephone announcements signposting appropriate patients with the common cold in the direction of community pharmacy or self-management reduced demand for general practice consultations. Methods: Patients telephoning a UK general practice to request an appointment between December 2017 and March 2018 heard announcements regarding management of the common cold. The percentage of callers choosing to continue to speak to a receptionist was compared with baseline data prior to the intervention. The mean waiting time to the third available routine general practice appointment during the intervention was compared with the previous year. Results: Routine calls continuing to reception reduced by 5.5 % (p<0.001) when the incidence of the common cold is at its highest and by 3.9% (p<0.001) throughout the intervention. The mean waiting time to the third available routine appointment reduced by 21%. Conclusion: This study has demonstrated that the use of telephone announcements signposting appropriate patients with the common cold in the direction of community pharmacy or self-management reduces calls to reception. This strongly infers that the telephone announcements reduce demand for general practice appointments and is supported by the reduced mean waiting time to the third available routine appointment. Implementation of this intervention could help general practitioners reduce seasonal demand in their own practices.